No increased inbreeding avoidance during the ovulatory phase of the menstrual cycle. (28th September 2022) - Holzleitner, Iris J.; Driebe, Julie C.; Arslan, Ruben C.; Hahn, Amanda C.; Lee, Anthony J.; O'Shea, Kieran J.; Gerlach, Tanja M.; Penke, Lars; Jones, Benedict C.; DeBruine, Lisa M.
Abstract: Abstract: Mate preferences and mating-related behaviours are hypothesised to change over the menstrual cycle to increase reproductive fitness. Recent large-scale studies suggest that previously reported hormone-linked behavioural changes are not robust. The proposal that women's preference for associating with male kin is down-regulated during the ovulatory (high-fertility) phase of the menstrual cycle to reduce inbreeding has not been tested in large samples. Consequently, we investigated the relationship between longitudinal changes in women's steroid hormone levels and their perceptions of faces experimentally manipulated to possess kinship cues (Study 1). Women viewed faces displaying kinship cues as more attractive and trustworthy, but this effect was not related to hormonal proxies of conception risk. Study 2 employed a daily diary approach and found no evidence that women spent less time with kin generally or with male kin specifically during the fertile phase of the menstrual cycle. Thus, neither study found evidence that inbreeding avoidance is up-regulated during the ovulatory phase of the menstrual cycle.